The university and its scientific production (Nexo Revista Científica, 2014)
The basic objective of the research activity is the creation of new knowledge and new products and services. Traditionally, and around the world, the creation of new knowledge is measured by the products (outputs) and impact (outcomes).DOI: http://dx.doi.org/10.5377/nexo.v27i2.1939